Creencias irracionales y su influencia en la depresión en una adolescente de 15 años - Checa Davila, Evelyn Isabel (2020)
In the present investigation a case study is presented that deals with the irrational beliefs that a 15-year-old adolescent has who is a student of the Educational Unit June 23 of the Baba Canton, since she presented changes that disturbed her social, emotional and family life and that these influenced depression, that is why I know that I set out to determine the irrational beliefs that influence depression, using psychological tools such as the Clinical History, the Beck Inventory, Inventory of Irrational Beliefs could be verified under the criteria that indicates the DSM - 5 that the diagnosis of this patient was major depression and thus a scheme of the psychotherapeutic process based on the Rational Behavioral Emotional Therapy could be made to be able to change those irrational beliefs that cause those insane emotions such as depression.